2013
DOI: 10.5604/17322693.1066062
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of selected phenols estimated by ABTS and FRAP methods

Abstract: Antioxidant properties of selected phenols in the ABTS test expressed as IC50 ranged from 4.332 μM to 852.713 μM (for gallic acid and 4- hydroxyphenylacetic acid respectively). Antioxidant properties in the FRAP test are expressed as μmol Fe2+/ml. All examined phenols reduced ferric ions at concentration 1.00 x 10-3 mg/ml. Both methods are very useful for determination of antioxidant capacity of water soluble phenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 0 publications
3
73
0
1
Order By: Relevance
“…ABTS is oxidized by potassium persulfate to its cation radical ABTS + , which is intensely colored. Our results showed that all the tested samples demonstrated a scavenging potential of the ABTS with varying inhibitory potential and interestingly, the MEHI demonstrating the highest ABTS inhibitory power and this result confirmed that the presence of higher phenolic level in the extract justified its highest scavenging property on ABTS radical [56]. Eventually, a good relationship was also observed between phenolics and antioxidant activity which further confirms this view [57].…”
Section: Discussionsupporting
confidence: 77%
“…ABTS is oxidized by potassium persulfate to its cation radical ABTS + , which is intensely colored. Our results showed that all the tested samples demonstrated a scavenging potential of the ABTS with varying inhibitory potential and interestingly, the MEHI demonstrating the highest ABTS inhibitory power and this result confirmed that the presence of higher phenolic level in the extract justified its highest scavenging property on ABTS radical [56]. Eventually, a good relationship was also observed between phenolics and antioxidant activity which further confirms this view [57].…”
Section: Discussionsupporting
confidence: 77%
“…The extract EEH had a significantly ( p < 0.05) more powerful inhibitory potential while the EFH and EFE extracts had the lowest scavenging potentials at all the concentrations. This result suggests that our extracted phytochemicals could act as radical scavengers owing to their hydrogen and electron donating capacity and their ability to delocalize/stabilize the resulting phenoxyl radical within the structure [40]. …”
Section: Resultsmentioning
confidence: 99%
“…•+ was observed for phenolics with three or more hydroxyl groups [Biskup et al, 2013]. The antioxidant activity depends on the number and position of the hydroxyl groups of the aromatic ring binding site and the type of a substituent [Ishige et al, 2001].…”
Section: Discussionmentioning
confidence: 99%